2014
DOI: 10.1590/1413-812320141911.15982013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of self-esteem among homosexuals in the southern region of the state of Santa Catarina, Brazil

Abstract: Evaluation of self-esteem among homosexuals in the southern region of the state of Santa Catarina, BrazilAvaliação da autoestima de gays do sul de Santa Catarina, Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Another reason may be the low level of awareness of the concept of lesbianism in secondary schools. This finding disagrees with some studies conducted by Canali et al, (2014) [23], Rosario et al, (2006) [24], Henderson, Simoni and Lehavot (2010) [25], which found a high practice of lesbian tendencies among ladies, and that both lesbians and heterosexual women possess a similar constellation of factors. The difference in the results may have been due to differences in the study areas as almost all these studies were conducted in foreign countries.…”
Section: Discussion Of Findingscontrasting
confidence: 94%
“…Another reason may be the low level of awareness of the concept of lesbianism in secondary schools. This finding disagrees with some studies conducted by Canali et al, (2014) [23], Rosario et al, (2006) [24], Henderson, Simoni and Lehavot (2010) [25], which found a high practice of lesbian tendencies among ladies, and that both lesbians and heterosexual women possess a similar constellation of factors. The difference in the results may have been due to differences in the study areas as almost all these studies were conducted in foreign countries.…”
Section: Discussion Of Findingscontrasting
confidence: 94%
“…Self‐esteem was assessed using the Rosenberg Self‐Esteem Scale (Rosenberg, 2015), which is a widely used self‐esteem measure in social science research and has been employed successfully on sexual minority populations (Canali et al., 2014). The scale consists of 10 items, such as "I feel that I have a number of good qualities" and "On the whole, I am satisfied with myself."…”
Section: Methodsmentioning
confidence: 99%
“…Most of the participants in the current study underlined that their self-esteem was dented by issues of homophobia and transphobia which is evident in other studies also (Taylor et al 2019 :19). There is however, contrasting findings as a study in Brazil found that high rates of self-esteem in a majority of the participants (Canali et al 2014 :4509). In the aforementioned study, the participants who were graded low in self-esteem also had additional adverse factors other than gender minority status (Canali et al 2014 :4509).…”
Section: Discussionmentioning
confidence: 88%
“…There is however, contrasting findings as a study in Brazil found that high rates of self-esteem in a majority of the participants (Canali et al 2014 :4509). In the aforementioned study, the participants who were graded low in self-esteem also had additional adverse factors other than gender minority status (Canali et al 2014 :4509).…”
Section: Discussionmentioning
confidence: 88%